An edge-based smoothed three-node composite plate element with refined zigzag kinematics. (15th October 2021) - Wimmer, Heinz; Celigoj, Christian
Abstract: The so called Refined Zigzag Theory (RZT) has proven to be one of the most promising theories for analyzing shear-elastic, laminated structures. Since its first appearance considerable efforts have been made in the development of numerical tools and the assessment of the theory. The present contribution focuses on the numerical assessment of a variant of a triangular plate element, which was presented for the first time in 2013 by Versino and co-workers. This element uses low order interpolation functions for the seven kinematic variables. While the deformations show a good convergence a very dense mesh is required to get stresses of satisfying accuracy especially near zones of warping constraints. An edge-based smoothed element technique (ES-FEM) is applied to improve the performance of this element. Several numerical tests are performed with regular and irregular meshes which have shown a significant improvement of the convergence rate of deflections for thick and thin plates respectively. In relation to the standard FEM the ES-version shows a lower sensitivity to mesh irregularities and more accurate stress results.